Real-Time Implementation of Hybrid Visible Light/Infrared Communications Supporting Full-Range Dynamic Dimming Control - Shixin Liu; Xiaodi You; Jian Chen; Changyuan Yu; Chaoran Xiong; Mingyi Gao; Gangxiang Shen (IEEE Photonics Journal)
Implementing dimming control in visible light communication (VLC) systems often involves a trade-off that reduces data rates. To address this, we propose a hybrid visible light (VL)/Infrared (IR) communication scheme that leverages pulse amplitude modulation (PAM) symbols in both VL and IR spectra, alternating them within pulse width modulation (PWM) “ON” and “OFF” slots. By efficiently using PWM “OFF” slots, the achievable data rate drop due to dimming is mitigated without affecting illumination. To ensure synchronization during the switch between VL and IR links, we design real-time dimming control state machines at both ends of the link, enhancing link stability. Additionally, we develop an adaptive hybrid frame structure that dynamically adjusts the length of transmitted information as the duty cycle continuously changes, ensuring uninterrupted communication. Experimental results from implementation using field-programmable gate arrays (FPGA) demonstrate real-time transmission under precise full-range dimming control, dynamically ranging from 1 to 0 with a resolution of 0.0053, maintaining a consistent 10 Mb/s data rate at bit error rates (BERs) lower than 3.4 × 10−4 and 20 Mb/s at BERs lower than 7.0 × 10−3 within a link range of 0.53 m without light concentration at the transmitter. Compared to baseline VLC, our system achieves a 100% data rate improvement at a duty cycle of 0.5, and supports stable data transmission even in low-light conditions.